To determination of the heights on geodynamic and technogenic polygons - Perovych, Lev; Perovych, Ihor; Perovych, Lesia; Ludchak, Oksana (Geodesy and Cartography, 2018)
When performing high-precision geometric leveling on geodynamic and technogenic polygons, the problem of selecting a system of heights and obtaining reliable data arises, taking into account, first of all, the heterogeneity of the gravitational field along the lines of leveling. The research and development of a methodological approach to solve the above issues is the purpose of this publication. For the research process, the method of mathematical processing of a wide spectrum of geodetic and gravimetric measurements, differential and mathematical analysis, methods of conducting high-precision leveling and gravimetric works are used. During the process of field geodetic and gravimetric measurements, the values of gravitational acceleration in the mountain, foothill and plain areas were obtained, which made possible, on the basis of the mathematical dependences deduced by the author, to find corrections in the measured excesses for the non-parallelism of the level surfaces. On the basis of unique experimental level-gravimetric observations and their corresponding mathematical elaboration, numerical characteristics of gravitational acceleration for various forms of relief have been obtained. In the final case, the obtained analytic dependencies give an opportunity to take into account the influence of the non-parallelism of the level surfaces in the measured excesses or the heights of high-precision geometric leveling, without taking into account the gravitational field of the normal Earth. The proposed methodological approach to the determination of heights by high-precision geometric leveling on geodynamic and technogenic polygons may take into account the influence of the non-parallelism of the level surfaces according to the derived formulas and should be effectively used at present.